Penguatan Kerangka Hukum Kebijakan Amnesti Massal dalam Mendukung Reformasi Sistem Pemasyarakatan - Hikmawati, Puteri (Jurnal Negara Hukum: Membangun Hukum Untuk Keadilan, 2025)
Overcapacity in correctional institutions (Lapas) remains a significant challenge in Indonesian correctional system. The proposed mass amnesty is considered a potential policy instrument to support correctional system reform to address this overcapacity issue. However, the current legal basis for implementing amnesty is still based solely on the 1945 Constitution of Indonesia, while in practice there has been a shift within the range of crimes that eligible for amnesty, as well as the potential for periodicmass amnesties to support the correctional system reform. Therefore, this article examines the role of mass amnesty policies in addressing the overcapacity issue. Furthermore, it analyzes the urgency of strengthening the legal framework on amnesty through the formulation of comprehensive legislation. This article is based on normative legal research, using various approaches, namely legislative, conceptual, and comparative approaches. The article indicates that the overcapacity issue is urgently needed to be addressed, and that mass amnesty, as a short-term solution, can be an appropriate policy instrument to address this problem. Mass amnesty has been commonly implemented in countries with overcapacity issue. Therefore, strengthening the amnesty regulations, particularly those designed to be administered periodically, is urgently needed to support correctional system reform in Indonesia.